Peran Badan Usaha Milik Pesantren Dalam Penguatan Ekonomi Pesantren Terhadap Pembangunan Berkelanjutan - Lailatul Ma’rifah; Zumaroh Zumaroh; Hermanita Hermanita; Primadatu Deswara (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Islamic Boarding School-Owned Enterprises (BUMP) are a strategic instrument in supporting the economic independence of Islamic boarding schools. However, in practice, BUMP management at Baitunnur Islamic Boarding School still faces various obstacles, especially in the management aspect and the desires of the business units. This study aims to analyze the role of BUMP in realizing the economic independence of Islamic boarding schools and identify problems that hinder the optimization of business units. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that BUMP contributes to increasing the economic independence of Islamic boarding schools and empowering students through direct involvement in business unit management. However, the main problem found is the suboptimal performance of several service business units due to the sender of requests and a weak management cadre system that causes a decline in business unit performance after a change of management. These findings indicate that BUMP has supported the achievement of sustainable development and SDGs Goal 1 at the micro level, but requires strengthening the management and cadre system to maintain the desire to do business.